Influence of Reading Interest and Emotional Intelligence on Learning Outcomes - Sri Susilawati; Farida Nugrahani; Suwarto (Tarbiyah Departement collaboration with AMCA, 2023)
This study aims to determine the influence of reading interest and emotional intelligence together on the learning outcomes of Indonesian both partially and simultaneously. This type of research is correlational quantitative because the research results will be calculated with statistical figures. The population in this study were all 168 students of class XI at State High School 1 Panggang. Based on the Slovin formula, the number of research samples is 119 respondents. The sampling technique uses simple random sampling or random. The data collection technique uses a questionnaire, namely a questionnaire of reading interest and emotional intelligence, as well as documentation to determine students' Indonesian language scores. The data analysis technique in this study used multiple regression analysis. Based on the analysis and discussion of the research results, the following conclusions can be drawn: (1) interest in reading influences the learning outcomes of Bahasa students in class XI at State High School 1 Panggang. (2) emotional intelligence influences the results of learning Indonesian for class XI students at Panggang 1 Public High School. (3) There is an influence of interest in reading and emotional intelligence together on the results of learning Indonesian for class XI students of State High School 1 Panggang. Â